Exploring the Significance of Vedānta Darśana in Cultivating Happiness and Well Being in Human Life (The Journal of Sindhuli Multiple Campus, 2026)
This paper explores the significance of Vedānta Darśana and its teachings in cultivating happiness and enhancing well-being. Eastern and Western philosophies approach the pursuit of happiness differently, a universally recognized goal. While Western perspectives, influenced by individualistic and capitalist values, dominate the current understanding of happiness, Eastern traditions such as Vedānta offer alternative insights. This paper critically analyzes the prevailing Western perspectives on happiness, focusing on psychological and economic viewpoints and discussing the limitations of these approaches. The study utilizes a review-based methodology, drawing from the scholarly literature on Vedānta and happiness. It examines its core teachings and concepts as presented in the Upaniṣads, Bhagavad-Gītā, and Brahma Sūtras. The paper also delves into the theoretical and philosophical frameworks of happiness and well-being, encompassing psychological perspectives, economic viewpoints, and the capability approach. Exploring the concepts of Ānanda (ultimate happiness) and Sukha (general happiness), the paper argues that these two constructs provide a deeper understanding and a sense of enlightenment, emphasizing the concept of 'Brahman' as the ultimate truth. While the study may not provide an exact framework for an alternative perspective on Vedānta's teachings, it does contribute to a foundational framework that explores the potential impact of Vedānta in fostering purpose, well-being, and inner transformation.